The role of some aquatic plants present on the banks of Al-Kabeer Al-Shamali River in lattakia governorate in transmission by parasitic helminths of man - مصري, عائشة; أمل إبراهيم ديوب,; عفيفة محمد عيسى , (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted on some aquatic plants distributed on the banks of Al-Kabeer Al-Shamali River in lattakia governorate in two regions (Amrouniyah and Al-Sinaa) with the aim of confirming whether a contamination with parasitic worm eggs in Al-Kabeer Al-Shamali River was present. Plant samples were collected twice during winter and spring seasons of 2023-2024. The samples were then examined in the lab using internationally approved laboratory methods to detect the presence of parasitic worm eggs.Five aquatic plant species were collected. Three species belonged to the Asteraceae family: wild dandelion (Cichorium intybus), saw lettuce (Lactuca serriola), and mistletoe (Inula viscosa), and one plant species was from the Polygonaceae family. It is the sorrel (Rumex crispus), and the fifth plant species (phragmites Sp) belonged to the Poaceae family.The results of the microscopic examination of the collected plants showed the presence of parasitic worm eggs: Ascaris lumbricoides, Taenia Sp., Hymenolepis nana, Hymenolepis diminuta, and Enterobius vermicularis.The results of the study showed that the eggs of the) Hymenolepis nana Hymenolepis diminuta) were the most predominant eggs of the baby worms. they were recorded on the common reed plant in both sites, and their overall number reached 102 eggs, followed by the eggs of Ascaris, with a total count of 15 eggs, the eggs of the, Taneia Sp 14 eggs, the Enterobius vermicularis, 11 eggs, respectively. The eggs were mostly predominant in spring compared to winter seasons.This is the first study in Syria to investigate the eggs of parasitic worms transmitted by aquatic plants, distributed on the banks of Al-Kabeer Al-Shamali River in lattakia governorate.